Circulating cell-free DNA and circulating tumor cells, the "liquid biopsies" in ovarian cancer - Xianliang Cheng; Lei Zhang; Yajuan Chen; Chen Qing (BMC, 2017)
Abstract Limited understanding of ovarian cancer (OC) genome portrait has hindered the therapeutic advances. The serial monitoring of tumor genotypes is becoming increasingly attainable with circulating cell-free DNA (cf-DNA) and circulating tumor cells (CTCs) emerging as "liquid biopsies". They represent non-invasive biomarkers and are viable, as they can be isolated from human plasma, serum and other body fluids. Molecular characterization of circulating tumor DNA (ct-DNA) and CTCs offer unique potentials to better understand the biology of metastasis and resistance to therapies. The liquid biopsies may also give innovative insights into the process of rapid and accurate identification, resistant genetic alterations and a real time monitoring of treatment responses. In addition, liquid biopsies are shedding light on elucidating signal pathways involved in invasiveness and metastasis competence; but the detection and molecular characterization of ct-DNA and CTCs are still challenging, since they are rare, and the amount of available samples are very limited. This review will focus on the clinical potential of ct-DNA and CTCs in both the early and advanced diagnosis, prognosis, and in the identification of resistance mutations in OC.